Development of a multipurpose GATEWAY-based lentiviral tetracycline-regulated conditional RNAi system (GLTR). - Reinhard Sigl; Christian Ploner; Giridhar Shivalingaiah; Reinhard Kofler; Stephan Geley (PLoS ONE)
RNA interference (RNAi) has become an essential technology for functional gene analysis. Its success, however, depends on the effective expression of RNAi-inducing small double-stranded interfering RNA molecules (siRNAs) in target cells. In many cell types, RNAi can be achieved by transfection of chemically synthesised siRNAs, which results in transient knockdown of protein expression. Expression of double-stranded short hairpin RNA (shRNA) provides another means to induce RNAi in cells that are hard to transfect. To facilitate the generation of stable, conditional RNAi cell lines, we have developed novel one- and two-component vector GATEWAY-compatible lentiviral tetracycline-regulated RNAi (GLTR) systems. The combination of a modified RNA-polymerase-III-dependent H1 RNA promoter (designated 'THT') for conditional shRNA expression with different lentiviral delivery vectors allows (1) the use of fluorescent proteins for colour-coded combinatorial RNAi or for monitoring RNAi induction (pGLTR-FP), (2) selection of transduced cells (pGLTR-S), and (3) the generation of conditional cell lines using a one vector system (pGLTR-X). All three systems were found to be suitable for the analysis of essential genes, such as CDC27, a component of the mitotic ubiquitin ligase APC/C, in cell lines and primary human cells.